PELATIHAN PEMBUATAN SEDIAAN OBAT TOPIKAL BERBAHAN DASAR HERBA VIRGIN COCONUT OIL (VCO) TANPA PEMANASAN DAN BAHAN KIMIA TAMBAHAN - Atin Supiyani; Dalia Sukmawati; Sri Rahayu (Politeknik Negeri Sriwijaya, 2022)
Virgin Coconut Oil (VCO) has long been known to have a lot of potential as herbal medicine for various diseases. Various studies have been conducted to find the best method for producing VCO. The use of heating techniques and the addition of various chemicals in the manufacture of VCO can have an impact on changing the quality of the VCO produced. Therefore, in this activity, training was carried out on the manufacture of herbal medicinal preparations based on VCO without heating and additional chemicals. The method uses a fermentation technique with coconut milk as raw material. The training was given on Saturday-Sunday, 18-19 September 2021 at the PKK Group RT 06 RW 05 Banjaran Pucung Village, Cilangkap, Tapos, Depok City. Making VCO using 20 coconuts, not peeled, squeezed with a squeezing machine. During the squeezing process, 2 liters of coconut water are added. The juice of 10 liters of thick coconut milk is used as an ingredient for making VCO. Coconut milk is then fermented by adding 1 liter of coconut water, tightly closed, and allowed to stand for 24 hours. VCO oil obtained through the filtering process can be used as a basic ingredient for herbal medicines directly or used as a solvent to add other herbal extracts. This training is expected to increase the knowledge and skills of housewives. The manufacture of herbal medicines based on VCO can be developed into a small household-level business that can be a source of additional income for the family.